La Teoría del Equilibrio Económico y Financiero de los contratos administrativos en Costa Rica - López Jiménez, Enrique (2014)
This study examines the application of the principle of economic and financial equilibrium of administrative contracts in Costa Rica. It especially emphasizes Constitutional Chamber’s jurisprudence. This paper reflects on five important issues: (1) Normative basis. (2) The concept of “risk” in the contractual relationship. (3) The concretization of the principle of economic equilibrium (principles of risk and venture, factum principis, ius variandi, sujétions imprévues, théorie de l’imprévision, price or tariff readjustment). (4) Readjustment methodologies. (5) Legal remedies.